2021
DOI: 10.2485/jhtb.30.303
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Sol-gel Synthesized Modulated 45S5-Bioglass Based Biodegradable Bone Graft Intended for Alveolar Bone Regeneration

Abstract: Reconstruction and augmentation of the alveolar bone defects pose a challenge for the dental surgeons due to its complex structure. The primary objective of tissue engineering is to regenerate or replace damaged tissues or organs including damaged bone tissues with bone grafts, cells, and biological molecules. 45S5-bioglass (45S5-BG), with its superior osteoconductive and osteoinductive abilities, has been at the forefront of tissue engineering, alveolar bone regeneration, and periodontal regenerative surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These weak peaks originate from HAp at 2θ ≈ 33°(024) and 46°(141), and a decrease in the intensity of the peaks were observed at 21 days and 28 days due to the lack of precipitation over time. [ 45,50,69,70 ] Shankwar et al showed in their study that when BG and PVA are mixed and electrospinning for a long time (>2 h) to obtain sufficiently thick composite nanofibrous membranes, the deposited phase can crystallize in nanocrystalline form and increase the bioactivity for the bone mineral phase in the membranes. [ 13 ] Thus, it was shown that the bioactivity of the CL‐PVA/3BG membranes produced in this study was successfully realized.…”
Section: Resultsmentioning
confidence: 99%
“…These weak peaks originate from HAp at 2θ ≈ 33°(024) and 46°(141), and a decrease in the intensity of the peaks were observed at 21 days and 28 days due to the lack of precipitation over time. [ 45,50,69,70 ] Shankwar et al showed in their study that when BG and PVA are mixed and electrospinning for a long time (>2 h) to obtain sufficiently thick composite nanofibrous membranes, the deposited phase can crystallize in nanocrystalline form and increase the bioactivity for the bone mineral phase in the membranes. [ 13 ] Thus, it was shown that the bioactivity of the CL‐PVA/3BG membranes produced in this study was successfully realized.…”
Section: Resultsmentioning
confidence: 99%
“…PLA colorless pellets were supplied by a filament producer company (Add North 3D AB, Stockholm, Sweden) and used for the production of the PLA-BG composite. The 1–4 dioxane was procured from Sigma Aldrich (Stockholm, Sweden), and 45S5 BG was synthesized via the sol–gel technique with an average particle size of 150 nm, as measured from transmission electron microscopy, that was stable up to 800 °C as reported in our previous studies [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…For in vitro cytotoxicity analysis, a 3-(4,5-dimethylthyazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used for the evaluation of cytotoxicity analysis, as reported in an earlier study [ 44 , 45 ]. The mouse L929 fibroblast cell line was seeded at 3 × 10 with 4 cells/mL in a 96-well plate and cultured using DMEM medium.…”
Section: Methodsmentioning
confidence: 99%
“…Going back to the pioneering sol-gel formulations by Li et al [28], all synthesized bioactive compositions were not fully glassy, as they contained some crystalline phases. Hence, to produce a completely amorphous 45S5 BG composition without crystalline inclusions using the sol-gel technique has been a challenge so far and several authors have reported the presence of calcium sodium silicate phases [183][184][185][186]. Faure et al [183] explored the use of citric acid instead of the usual nitric acid for the synthesis of the 45S5 formulation, but revealed a partial crystallization of Na 2 Ca 2 Si 3 O 9 , Na 2 Ca 3 Si 6 O 16 and Na 2 CaSi 2 O 6 inside the amorphous structure of the BG.…”
Section: Compositions and Chemical Routesmentioning
confidence: 99%